Aspect Of Consumer Protection Against Circulation Of Hard Drug In The Market (Study At BPOM Medan) - Nova Liani Munthe (Journal of Law Science, 2021)
Consumer protection is a matter of human interest, therefore it is a hope for nations in the world to be realized. Thus the importance of the issue of Consumer Protection in Indonesia, then issued a statutory regulation, namely Law no. 8 of 1999 concerning the Consumer Protection Act (known as UUPK). Especially Consumer Protection in the Health Sector which is something that is really needed by consumers in obtaining drug products circulating in the community, where the circulating drug products have been supervised by an agency that can be responsible for drug control. The Food and Drug Supervisory Agency (BPOM) is an agency appointed by the government in conducting drug control, The problems that will be discussed are first, how is the function of BPOM in Consumer Legal Protection. Second, how is consumer protection against the use of hard drugs. Third, what legal remedies can be taken by consumers as a result of losses in the use of strong drugs. The author obtains data and materials regarding the problems discussed, the author conducts Library Research, namely obtaining materials through reading sources or written materials as data of a scientific theoretical nature or secondary data. The author also conducts empirical research, namely obtaining data directly and conducting studies based on facts that occur in the field. Finally, conclusions were obtained, among others, first, the function of the Supervisory Board Drug and Food (BPOM) is to carry out control and supervision in the field of medicine and food. BPOM became aNon-Departmental Institution (LPND). Second, the role of the government is very necessary, namely by making a policy regarding food (food) which is carried out in an effort to control, supervise, develop and educate consumers and business actors. And invites consumers to think smart in consuming and using drugs, so that they are in accordance with the dose recommended by the doctor so they don't buy in any place. Third, legal remedies that can be taken by consumers are litigation or non-litigation, where non-litigation methods can be through the Dispute Resolution Agency (BPSK).